Universiti Malaysia Pahang obtained five-star ratings - Irene, Wei Kiong Ting (2018)
In the Malaysian Ministry of Higher Education’s recently-released Malaysia Research Assessment (MyRA), Universiti Malaysia Pahang (UMP) did very well and received the five star rating of the MyRA for the year 2017 by virtue of its research development and commercialization programs.